The Relationship Between Parental Social Support and Academic Stress in University Students: Hubungan Antara Dukungan Sosial Orang Tua dengan Stress Akademik pada Mahasiswa di Universitas - Mukti, Salsabila Ayu Setyo; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2023)
The research was stimulated by the phenomenon of academic stress experienced by students. The purpose of the study was to determine the relationship between parental social support and academic stress in students of the Faculty of Science and Technology, Universitas Muhammadiyah Sidoarjo. Hypothesis proposed that there is a negative connection between parental social support and academic stress on students. There are 312 samples in this research from a total population of 2218 students. Sampling was done by using purposive sampling technique. The research insrumet used is the scale of parental social support dan stress academic with the Likert model. Data analysis using Pearson's Product Moment Correlarion Technique with the help of SPSS 21.0 software. The results of the data analysis of this research showed a correlation coefficient (rxy) of -195 with a significance of 0.001 < 0.05, which means that there is no relevance between parental social support and academic stress on students. This indicates that the higher the parental social support, the lower the academic stress experienced by students. In contrast, the lower parental social support the higher the academic stress experienced by students. The results of this study shows that parental social support has an influence on academic stress by 3.8%.